Effectiveness of a workplace health promotion program in reducing obesity: a retrospective study - Reinoso-Barbero, Luis; Muñoz-Dueñas, Pilar; Caro Rodríguez, Inmaculada; Araujo, Sofia; Gómez-Paredes, Laura; Muñoz-Gutiérrez, Juan; Pérez-Herreras, Cristina; Gómez-Gallego, Félix (Journal of Occupational and Environmental Medicine, 2026)
Objective This retrospective study aimed to evaluate the effectiveness of a workplace health promotion program targeting obesity. Methods Weight loss, body mass index (BMI), and abdominal circumference were measured before and after the program during medical check-ups at a single workplace. Thirty-six employees (BMI ≥30 kg/m2) received 6 months of free telemedicine endocrinology consultations. This metrics were compared with 164 workers (BMI ≥ 30 kg/m2) using the Student t test and odds ratio. Results Participants lost more weight (1.98 kg on average vs 0.11 kg), OR: 1.5 (0.72–3.12), BMI (0.84 kg/m2 vs 0.03 kg/m2), OR: 2.16 (0.99–4.68), and abdominal circumference (1.06 cm vs 0.55 cm), OR: 1.07 (0.51–2.25) than nonparticipants. Conclusions The program was slightly more effective than standard verbal and written medical advice given during check-ups. Studies with bigger sample sizes are needed to support these findings.
Keywords: occupational health; obesity/overweight; workplace; health promotion; telemedicine